The effect of haloxyfop-R-methyl ester and imazamox herbicides, tine or no tillage and nine different medic cultivars on the seed and dry matter production as well as the quality of medic pastures - Beyers, Hendrik Philippus (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--University of Stellenbosch, 2001.